METHODOLOGICAL APPROACH TO MANAGEMENT OF STRATEGIC AND INNOVATIVE DEVELOPMENT OF COAL INDUSTRY - Drachuk, Yu. Z.; Rassuzhdai, L. M. (Visnyk of Vinnytsia Politechnical Institute, 2013)
Functions of industry development management, the basic principles of its innovation policy and concept of strategy of building scientific and technological innovation and development of the domestic coal industry are considered in the paper. Attention is focused on taking into account the need of property relations reformation in order to attract private (collective) capital in the activities of an increasing number of subjects of the coal industry.